Evolutionaries : unlocking the spiritual and cultural potential of science's greatest idea - Phipps, Carter (Harper Perennial, 2012)
"When it comes to evolution, we've all heard about fossils and fruit flies, Darwin and Dawkins. But the idea of evolution is far more profound-and far-reaching. Today, a movement of visionary scientists, philosophers, and spiritual thinkers is forging a new understanding of evolution that honors science, reframes culture, and radically updates spirituality. Carter Phipps calls them Evolutionaries."--P. [4] of cover.